Friction stir processing combined with incremental forming effect on AA2014-T6. Issue 8 (11th June 2021) - John, Jacob; Shanmuganatan, S. P.; Kiran, M. B.; Senthil Kumar, V. S.; Krishnamurthy, R.
ABSTRACT: The present-study accustomed aluminum 2014-T6 alloy of 3 mm sheet as the work material for conducting the friction stir processing. The entire studies have been completed in two phases of work. In the first phase, the work material is subjected to single-pass and multi-pass friction stir processing for its structural embattlement. A multi-faceted tool called hexagonal tool pin profile was preferred to carry out the stir processing for both the single and multi-pass cases. An optimized stir processing parameters essentially tool-speed 1000 rpm, table-feed 60 mm/min and 2° pivot angle were selected to carry out the stir processing. In the second phase, the single-pass FSPed and multi-pass FSPed work samples along with an unprocessed base metal are subjected to single point incremental forming process for its performance assessment on formability. The effect of forming parameters on average thickness, wall angle, forming limit strains and surface roughness have been analyzed on the profile forming of a cylindrical cup. To characterize the nature of profile formed structures, metallurgical, grain analysis and micro-hardness studies have been carried out at different locations of the formed segments. Conforming to the results, multi-pass FSPed samples exhibit superior formability followed by single-pass and least in the unprocessed sample.